Analysis of Damage (Speed Drop) in Electric Vehicles Using Matlab Simulation - Mariani, Dina; Saptadi, Arief Hendra; Sumarno, Radiktyo Nindyo (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Electric bicycles have become a popular mode of transportation among modern society. Many people are starting to use electric bicycles, especially for needs around the home environment. However, like other vehicles, electric bicycles can also experience damage that can affect their performance. One of them is the problem of speed drops on electric bicycles, where the bicycle suddenly slows down even though the battery is not empty. This research on electric bicycles aims to analyze and overcome problems that often occur on electric bicycles, especially speed drops. The research method used is a case study by conducting tests and analysis on electric bicycles that experience speed drops and simulating them with matlab. The results of the study showed that the main cause of speed drops on electric bicycles was damage to the battery and charging system, causing an imbalance in the voltage of the four batteries. One of the batteries has a voltage of 12.71V so that the State of Charge (SoC) value of the damaged battery will be a benchmark for the other three batteries. The results of this study are expected to provide useful information for electric bicycle users to improve the quality of electric bicycle use.Sepeda listrik telah menjadi moda transportasi yang popular di kalangan masyarakat modern. Masyarakat mulai banyak yang menggunakan sepeda listrik terutama untuk keperluan di sekitar lingkungan rumah. Namun, seperti halnya kendaraan lainnya, sepeda listrik juga bisa mengalami kerusakan yang dapat mempengaruhi performanya. Salah satunya adalah masalah drop kecepatan pada sepeda listrik, dimana sepeda tiba-tiba mengalami perlambatan padahal kondisi baterai belum kosong. Penelitian tentang sepeda listrik ini bertujuan untuk menganalisa dan mengatasi masalah-masalah yang sering terjadi pada sepeda listrik terutama masalah drop kecepatan. Metode penelitian yang digunakan adalah studi kasus dengan melakukan pengujian dan analisis pada sepeda listrik yang mengalami drop kecepatan dan mensimulasikannya dengan matlab. Hasil penelitian menunjukkan bahwa penyebab utama terjadinya drop kecepatan pada sepeda listrk adalah kerusakan pada baterai dan sistem pengisian daya sehingga menyebabkan adanya ketidakseimbangan tegangan dari keempat baterai. Salah satu baterai memiliki tegangan 12.71V sehingga nilai State of Charge (SoC) dari baterai rusak tersebut akan menjadi patokan bagi ketiga baterai yang lain. Hasil penelitian ini diharapkan dapat memberikan informasi yang bermanfaat bagi pengguna sepeda listrik untuk meningkatkan kualitas penggunaan sepeda listrik.